Crises, Volatility, and Growth - Kharroubi, Enisse (World Bank, 2012)
When credit is constrained, a bias toward short-term debt can arise in financing long-term investments, generating maturity mismatches and leading potentially to liquidity crises. After the financial crises of the 1990s many voices rose to explain that the causes of these crises were new (Radelet and Sachs 1998; Corsetti, Pesenti, and Roubini 1999). According to the first, "crony capitalism" can explain the imbalances (Krugman 1999), because in distorting individual incentives, it encouraged firms to make inefficient decisions (about investments, risks, and so on). Understanding how economic and financial development modifies financial contracts requires understanding original sin. THE MACROECONOMIC MOD EL This section introduces this capital market framework in a macroeconomic model to shed light on the aggregate consequences of the structure of financial contracts. Long-term contracts are imperfectly enforceable; default is possible, but an entrepreneur needs to pay a marginal cost on the final output (t when the entrepreneur can carry out an illiquid long-term project and t when the entrepreneur violates the illiquidity constraint and reinvests in the storage technology). The case where entrepreneurs pay for their debts if and only if they can carry out their illiquid project until maturity (not considered here) is always dominated; entrepreneurs have to pay for default costs and there are no benefits for the debt portfolio (size being identical and risk premium being actuarially fair). These two sources of aggregate volatility reduce growth through independent channels; the probability of a run reduces the average return on the entrepreneur's projects, whereas the volatility R 2 r on the return on entrepreneur's projects increases the average return on the entrepreneur's projects but imposes a negative effect on the storage technology that always dominates at the aggregate level. Interaction Effects of Financial Development and Different Volatility Measures Dependent variable: GDP per capita growth Regression 1 Log of initial GDP per capita Population growth Credit to GDP Growth volatility Low-growth frequency Growth volatility Â credit to GDP Low-growth frequency Â credit to GDP Hausman test (p-value) Sargan test (p-value) Number of observations 2 3 4 5 6 20.965** 20.728*** 20.657** 20.738*** 20.790*** 20.995** 20.894*** 20.634** 20.774*** 20.506** 21.974*** 20.724*** -- 1 À a l ars m t 458 THE WORLD BANK ECONOMIC REVIEW If an entrepreneurs can carry out a project in the production technology with a debt portfolio (a,m), it is then incentive-compatible to exchange this portfolio against a portfolio (b,m) if and only if (1 m 2 bmrs)R 2 2 t).